Personal infection prevention behaviors and campaign to encourage travel during COVID-19: A cross-sectional study - Shimoda, Hayato; Nagata, Tomohisa; Ishimaru, Tomohiro; Hino, Ayako; Ando, Hajime; Muramatsu, Keiji; Tateishi, Seiichiro; Tsuji, Mayumi; Mori, Koji (Frontiers in Public Health, 2023)
Introduction: The Go To Travel campaign in Japan was launched to subsidize travel and accommodation costs for tourists through vouchers that could be used at domestic destinations. Infection prevention behavior can lead to refraining from travel owing to infection concerns; conversely, taking preventive action can promote travel. There is a lack of information about the association between infection prevention behaviors and desire to travel. Thus, we examined the relationship between personal infection prevention behaviors and using Go To Travel. Methods: We conducted a cross-sectional study of 26,637 workers who responded to a large-scale questionnaire survey about COVID-19 in Japan. We built multilevel logistic regression models adjusted for confounders to assess the association between the number of personal infection prevention behaviors and using Go To Travel. Further, we adjusted for fear of COVID-19 infection as a confounding factor and evaluated its impact. With the same model, we also analyzed the association between each personal infection prevention behavior and using Go To Travel. Results: Among the 26,637 participants, 7,959 (30%) used Go To Travel. The odds ratio for the group practicing 4–5 preventive behaviors to that of the group adopting 0–1 behaviors was 1.32 (95% confidence interval, 1.05–1.65); the odds ratio for the group practicing 6–7 behaviors was 1.27 (95% confidence interval, 1.02–1.59). The behaviors we found to be associated with using the Go To Travel campaign were wearing a mask when among other people, disinfecting hands with alcohol before going indoors, carrying an alcohol sanitizer, and disinfecting hands after touching objects outside. Conclusions: We observed a tendency for participants who closely complied with personal infection preventive behaviors to use Go To Travel. However, many participants adopted inadequate daily infection prevention behaviors; thus, it is necessary to continue strongly encouraging the application of infection prevention behaviors at travel destinations.